Entomophagous of xylophilous insects of the State National Natural Park "Ile-Alatau" (Experimental biology, 2016)
For complex xylophilous insects of the State National Natural Park «Ile-Alatau» 52 species of entomophagous, belonging to 41 genus, 22 families and 5 orders found. Greatest diversity of beetles (Coleoptera) (24 species, 11 families), followed by Wasps (Hymenoptera) (17 species, 4 family – Ichneumonidae, Braconidae, Pteromalidae, Formicidae), Bugs (Heteroptera) (6 species, 4 families – Reduviidae, Pentatomidae, Lygaeidae, Anthocoridae), Flyes (Diptera) (4 species, 2 families – Asilidae, Xylophagidae) and Snakefly (1 species, 1 family Raphidiidae) different.
Keywords: entomophagous; xylophilous insects; State National Natural Park; Ile-Alatau; order; families; genera; species.